Rate Maximization for Multiband OFDM Ultra Wideband Systems Using Adaptive Power and Bit Loading Algorithm - Liaoyuan Zeng; McGrath, S.; Cano, E. (2009 Fifth Advanced International Conference on Telecommunications, 2009)
A new design for maximizing the data rate of the multiband orthogonal frequency division multiplexing ultra wideband systems is presented. The design is based on the generation of a series of M-ary quadrature amplitude modulation zones for each UWB subcarrier whose levels of fading depend on the UWB channel model. The available transmitted power is then optimally distributed to use the modulation scheme with the maximum M in the subcarriers. The optimization is constrained by the target bit error rate and the limitation of the UWB transmit power spectral density in each subcarrier. The rate maximization has been obtained in a three-step algorithm consisting of M-QAM zones generation, primary and advanced power and bit loading. The performance of the proposed algorithm is analyzed over UWB channel. The results show that the data rate is significantly improved by an advanced power and bit loading scheme.